1991
DOI: 10.1152/ajpcell.1991.261.1.c51
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Cl channel blockade by three classes of compounds

Abstract: We compared the potency and inhibitory actions of three different classes of organic acids on a Cl channel derived from colonic enterocyte plasma membrane vesicles. Chloride channels were incorporated into planar lipid bilayer membranes to examine the effects of the anthranilic acids, diphenylamine 2-carboxylic acid (DPC) and 5-nitro-2-(3-phenylpropylamino)benzoic acid (NPPB), the indanyl alkanoic acids, 2-[(2-cyclopentyl-6,7-dichloro-2,3-dihydro-2-methyl-1-oxo-1H-inden -5-yl)oxy] acetic acid (IAA-94) and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 6 publications
1
28
1
Order By: Relevance
“…This high conductance ORCC became active even when [Ca 2ϩ ] was buffered to 0.1 M (Fig. 2D) (23) and 100 M diphenylamine-2-carboxylic acid (24) are reported to inhibit ORCC in some cell preparations, these drugs did not prevent the appearance of ORCC in our experiments (data not shown).…”
Section: Purinergic Activation Of a 1-ps CLmentioning
confidence: 54%
“…This high conductance ORCC became active even when [Ca 2ϩ ] was buffered to 0.1 M (Fig. 2D) (23) and 100 M diphenylamine-2-carboxylic acid (24) are reported to inhibit ORCC in some cell preparations, these drugs did not prevent the appearance of ORCC in our experiments (data not shown).…”
Section: Purinergic Activation Of a 1-ps CLmentioning
confidence: 54%
“…The large Cl -currents in the presence of GST-syn 1A∆C were not affected by DIDS, which blocks a number of Cl -channels other than CFTR (26). Conversely, diphenylamine carboxylate (DPC), which does block CFTR Cl -channels (27), completely inhibited the currents that were potentiated by GST-syn 1A∆C ( Figure 5).…”
Section: Syntaxin 1a Resides At the Apical Poles Of Airway Epithelialmentioning
confidence: 98%
“…Single channel current records of rectifying colonic C1-channels in planar phospholipid bilayers were obtained as previously described (Reinhardt, Bridges, Rummel, and Lindemann, 1987;Bridges, Worrell, Frizzell, and Benos, 1989;Bridges and Benos, 1990;Singh et al, 1991). We used conventional polystyrene chambers for painted bilayers that were modified so the volume of each bath was 0.4 ml.…”
Section: Bilayer Techniquementioning
confidence: 99%
“…Having shown that TNP-ATP blocked the rectifying colonic C1-channel from either side, we performed event duration analysis to determine if TNP-ATP block con- closed time histograms obtained from current records before blocker addition could be described by single exponentials with an open time constant (%) of 270 -20 ms and a closed time constant (re) of ~3.0 ms (Reinhardt et al, 1987;Bridges et al, 1989;Singh et al, 1991 Second, % l should vary as a linear function of the blocker concentration with a slope corresponding to the on rate constant (kon). Third, the blocker should produce an additional exponential distribution in the closed time histograms corresponding to the blocked time constant ('rB).…”
Section: Tnp-atp Is An Open Channel Blockermentioning
confidence: 99%
See 1 more Smart Citation